Meta-analysis and trial sequential analysis of ezetimibe for coronary atherosclerotic plaque compositions - Chai, Bofeng; Shen, Youlu; Li, Yuhong; Wang, Xiaoyu (Frontiers in Pharmacology, 2023)
Background: Lipid aggregation, inflammatory cell infiltration, fibrous cap formation and disruption are the major causes of atherosclerotic cardiovascular disease (ASCVD) and the pathologic features of atherosclerotic plaques. Although ezetimibe's role in decreasing blood lipids is widely known, there isn't determine which part of the drug's influence on atherosclerotic plaques compositions. Objective: To systematically evaluate the efficacy of ezetimibe for coronary atherosclerotic plaque compositions. Methods: Two researchers independently searched the PubMed, Embase, Cochrane Library, and Web of Science databases for randomized controlled trials (RCTs) on the efficacy of ezetimibe for coronary atherosclerotic plaque from inception until January 22,2023. The Meta-analysis and trial sequential analysis (TSA) were performed using Stata 14.0, TSA 0.9.5.10 Beta software respectively. Results: 4 RCTs were finally included this study, which comprised 349 coronary artery disease patients. Meta-analysis findings showed that compared with control group, treatment group intervention measures could effectively reduce fibro-fatty plaque volume (FFP) [WMD=-2.90, 95%CI(-4.79, -1.00), P=0.003＜0.05]; there were no significant difference in the reduction of fibrous plaque volume (FP) [WMD=-4.92, 95%CI(-11.57, 1.74), P=0.15＞0.05], necrotic core volume (NC) [WMD=-2.26, 95%CI(-6.99, 2.46), P=0.35＞0.05], and change dense calcification volume (change DC) [WMD=-0.07, 95%CI(-0.34, 0.20), P=0.62＞0.05]between the treatment group and the control group. TSA findings showed more studies are still required to confirm the efficacy of ezetimibe for FP and NC in the future. Conclusions: Compared to the control group, ezetimibe significantly decreased FFP, but it had no statistically significant difference on FP, NC, and change DC. According to TSA, further research will be required to confirm the efficacy of ezetimibe for FP and NC in the future.